(3GdeMGSHI GdVQjHjI Hjf GdfXQjI h GdJWHjbs - (3eMeO YHGS(B, (3HOhjs ((3GdGScfOQjI(B:s (3OGQ GdLGeYI GdLOjOI(B,s, 2005)
(3GdeMGhQ GdGSGSjI GdJMGSH Yf GdVQjHI GdehVhYjI ddONd h GYJHGQGJ JMOjO GjQGOGJ GdfTGW GdJLGQj h GdUfGYj h TQhW NVhYgG ddVQjHI h fWGb GjQGOGJ GdfTGW GdJLGQj h GdUfGYj GdNGVYI ddVQjHI , GdGSS GdYGeI dbjGS GdQHM GdVQjHj h bjGS GdQHM GdVQjHj ddfTGW GdJLGQj h GdUfGYj (B((3GdGjQGOGJ GdNGVYI ddVQjHI h GdJcGdja h GdeHGdZ GdhGLHI GdNUe , JMOjO eG jONd aj hYGA GdVQjHI GdehMOI ef CQHGM GdfTGW GdJLGQj h GdUfGYj eY GdNUe h GdGVGaI h GdJMUjd dMSGH GdVQjHI , GYJHGQGJ JMOjO GjQGOGJ fTGWGdegfZjQ GdJLGQjI h TQhW NVhYgG ddVQjHI h bjGS GdQHM GdVQjHj dfTGW Gdegf ZjQ GdJLGQjI h GdJRGeGJ Gdeehdjf h GdNUe h GdJMUjd dMSGH GdVQjHI , GdJMGSH GdVQjHI Yf GjQGOGJ GdGQGVj GdRQGYjI h GdYbGQGJ GdeHfjI h GdJMUjd dMSGH GdVQjHI h GSJfRGd GdVQjHI GdYbGQjI , GdJMGSH GdVQjHj Yf GjQGOGJ QDhS GdGehGd GdefbhdI h Yf GdeQJHGJ h eGaj McegG , GdJMGSH GdVQjHj Yf CQHGM TQcGJ GdGehGd h GdJMGSH Yf GdVQjHI GdYGeI Ydi GdeHjYGJ (B.s
Keywords: (3GdVQjHIs; (3GdVQjHI Ydi GdONds; (3GdeMGSHIs